Faktor Yang Mempengaruhi Kelelahan Kerja Pada Perawat IGD Di Rumah Sakit Islam Sunan Kudus Tahun 2024 - Nailatur Rida; Edy Soesanto; Heny Siswati (Journal of Innovative and Creativity, 2025)
Background: One of the main factors causing work accidents due to human error is work fatigue. Every year around the world, millions of accidents occur, ranging from the mildest to the most severe. These losses are incredibly severe. Work fatigue in hospitals includes fatigue caused by physical factors such as temperature, lighting, microorganisms, chemicals, noise, and circadian rhythm (the sleep-wake cycle that repeats approximately every 24 hours, especially in night shift nurses), while non-physical fatigue is caused by psychosocial factors both at work and at home or in the surrounding community. Purpose: To determine the influence of gender, age, and wor experience on work fatigue among emergency room nurses at RSI. Sunan Kudus in 2024. Objective : The type of research used is correlational analytic research with a cross-sectional time approach. This study uses Total Sampling. Researchers used this technique because the population of nurses in the RSI Sunan Kudus Emergency Department in 2025 was 37 respondents. The instrument used in this study is a questionnaire. The collected data was then analyzed using multivariate, univariate, and bivariate analysis, while the Spearman Rank Test was used to test the hypotheses. Result : The research results indicate a relationship between age range, gender, marital status, and work experience and work fatigue in emergency room nurses at RSI Sunan Kudus in 2024, with p-values of 0.038 < α = 0.05 for age range, 0.047 < α = 0.05 for gender, and 0.050 < α = 0.05 for marital status. The correlation coefficient values are 0.189 for gender with weak strength, 1.00 for age range with very strong strength, 0.690 for marital status with strong strength, and 0.00 for work experience with no relationship. Conclusion : Between gender, age range, and marital status, there is a relationship with work fatigue in ER nurses at RSI Sunan Kudus in 2024, while work experience has no relationship with work fatigue in ER nurses at RSI Sunan Kudus in 2024.